Knowledgeability, Attitude and Practice Behaviors of Dental Providers Toward Provisions of Integrated Care Delivery for Patients With Prediabetes/Diabetes: Wisconsin Statewide Survey - Shimpi, Neel; Panny, Aloksagar; Glurich, Ingrid; Chyou, Po-Huang; Acharya, Amit (Frontiers in Dental Medicine, 2021)
Introduction: To conduct a statewide survey among Wisconsin-based dental providers evaluating current knowledgeability, attitudes and practice behaviors surrounding management of patients with diabetes/prediabetes in the dental setting. The study explored perceptions on feasibility, value, barriers, and current status of integrated care model (ICM) adoption by dental practices Materials and Methods: A 32-question paper-based survey was mailed to all licensed dentists and dental hygienists practicing in Wisconsin. The study was conducted over a four-week period in 2019. The survey instrument was adapted from a previous validated survey and was expanded to include questions on ICM adoption. Content and validity analyses and beta testing were conducted prior to dissemination of the survey. Descriptive statistics and chi-square tests were applied for data analyses. Thematic analyses was performed on open-ended questions. Results: Survey response rate was 12% (N=854/7,356) representing 41% dentists and 59% dental hygienists. While 68% reported educating patients on oral health-diabetes associations, only 18% reported medical consultations to inform dental treatment, and ‘frequent’ (22%) or ‘occasional’ (40%), medical triage. Knowledge-based questions were correctly answered by >70% of participants. While 50% valued chairside glycemic screening and 85% supported non-invasive chairside screening to identify at-risk patients,>88% relied on patient-reported diabetic status. Barriers to ICM adoption included time investment (70%), patient activation/cooperation (62%), cost (50%), insurance coverage (50%), infrequent interdisciplinary communication (46%), lack of equipment (33%) and provider (31%). Conclusion: Low rates of ICM adoption, chairside testing, medical consultation and triage, and need for educational curricula reform were identified.